Effects of Self-Awareness and Sense of Belonging on Teachers' Professionalism - et. al., Erna Kusumawati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research was to determine the relationship between self-awareness and a sense of belonging to teachers' professionalism. The study strategy used is a quantitative correlation involving as many as 32 teachers in research subjects. By purposeful sampling, the subjects were chosen. Self-awareness scale, Sense of Belonging Instrument (SOBI), and scale of professionalism are the tools used. Analysis of data using partial correlation testing. The findings showed that there is a connection between self-awareness and significant professionalism with very strong criteria for correlation. However, with very low criteria for correlation, there is no significant relationship between a sense of belonging and professionalism. Then there is an important connection with low correlation criteria between self-awareness and a sense of belonging with professionalism. Each relationship has a positive direction for the relationship. The relationship between self-awareness, sense of belonging, and professionalism is clarified in this study.